Large-scale peculiarities of the temperature and salinity fields of the sea surface along the route of the Seventh Ukrainian Antarctic Expedition - Artamonov, Yu.; Perov, A. (Ukrainian Antarctic Journal, 2003)
On the basis of the hydrological data received during the 7th Ukrainian Antarctic Expedition in January-March, 2002, the large-scale peculiarities of the temperature and salinity fields of the sea surface in the Atlantic Ocean and Mediterranean sea are described. Sea surface front peculiarities are discussed. Seasonal changes of hydrological parameters in the tropical and middle latitudes of the Atlantic Ocean were determined.